A numerical investigation of the resin flow front tracking applied to the RTM process - Souza, Jeferson Ávila (2013)
Resin Transfer Molding (RTM) is largely used for the manufacturing of high-quality composite components and the key stage during processing is the resin infiltration. The complete understanding of this phenomenon is of utmost importance for efficient mold construction and the fast production of high quality components. This paper investigates the resin flow phenomenon within the mold. A computational application was developed to track the resin flow-front position, which uses a finite volume method to determine the pressure field and a FAN (Flow Analysis Network) technique to track the flow front. The mass conservation problem observed with traditional FE-CV (Finite Element-Control Volume) methods is also investigated and the use of a finite volume method to minimize this inconsistency is proposed. Three proposed case studies are used to validate the methodology by direct comparison with analytical and a commercial software solutions. The results show that the proposed methodology is highly efficient to determine the resin flow front, showing an improvement regarding mass conservation across volumes.